KONEKSI POLITIK, TEKANAN PEMERINTAH DAN FAKTOR LAIN YANG MEMENGARUHI PENGUNGKAPAN LAPORAN KEBERLANJUTAN - Jelanni, Evan; Rahayuningsih, Deasy Ariyanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The purpose of this research is to analyze the effect of profitability, liquidity, political connection, government pressure, firm size, board of director, and audit committee on sustainability report disclosure at companies listed on the Indonesia Stock Exchange from 2021 to 2023, using the Statistical Package for the Social Sciences (SPSS) with multiple regression analysis. The result of this research indicates that profitability, political connection, government pressure, board of director, and audit committee have no effect on sustainability report disclosure. While, firm size and liquidity have an effect on sustainability report disclosure. Firm size positively influenced the disclosure, as larger companies with more resources and a wider reach tend to enhance their legitimacy from societal perspective through sustainability report disclosure.